ANALISIS BIAYA DAN STRATEGI PENGEMBANGAN OBJEK WISATA MATANG KALADAN, KABUPATEN BANJAR - Mayske Ellora Anggraeni; Muhammad Helmi; Fonny Rianawati (Universitas Lambung Mangkurat, 2023)
Matang Kaladan Tourist Attractions one of the tourist destinations has an attraction in South Kalimantan. Matang Kaladan Tourism presents a view above the peak, so that it attracts visitors or tourists to come, and there are facilities in the form of photo spots that allow management at the Kaladan Matang Tourism location. The purpose of this study (1) analyzes management costs and revenues obtained from 2019-2021, (2) analyzes tourism development through SWOT methods and determines its development strategy. The methods used in this research cost analysis and SWOT. The results of the analysis of the cost of managing Kaladan Mature Tourist Attractions show the value of ratio = 1 in 2019 and 2020, and in 2021 shows the value of the ratio>1